2016
DOI: 10.1111/gcb.13522
|View full text |Cite
|
Sign up to set email alerts
|

Range shifts or extinction? Ancient DNA and distribution modelling reveal past and future responses to climate warming in cold‐adapted birds

Abstract: Global warming is predicted to cause substantial habitat rearrangements, with the most severe effects 1 expected to occur in high-latitude biomes. However, one major uncertainty is whether species will be 2 able to shift their ranges to keep pace with climate-driven environmental changes. Many recent studies 3 on mammals have shown that past range contractions have been associated with local extinctions rather 4 than survival by habitat tracking. Here, we have used an interdisciplinary approach that combines 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 49 publications
(69 reference statements)
3
19
0
Order By: Relevance
“…Among terrestrial organisms, high-elevation cold-adapted species seem to be particularly vulnerable to climate change (Dirnböck et al, 2011;Lagerholm et al, 2017), with their future distribution being either expected to contract towards higher elevations due to ambient temperature warming (La Sorte and Jetz, 2010;Braunisch et al, 2013;Chamberlain et al, 2013;Pernollet et al, 2015;Sekercioglu et al, 2008), or to vary in a complex way in response to shifts in precipitation regimes that remain difficult to forecast (e.g. Tingley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among terrestrial organisms, high-elevation cold-adapted species seem to be particularly vulnerable to climate change (Dirnböck et al, 2011;Lagerholm et al, 2017), with their future distribution being either expected to contract towards higher elevations due to ambient temperature warming (La Sorte and Jetz, 2010;Braunisch et al, 2013;Chamberlain et al, 2013;Pernollet et al, 2015;Sekercioglu et al, 2008), or to vary in a complex way in response to shifts in precipitation regimes that remain difficult to forecast (e.g. Tingley et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…This combined approach has proven a powerful tool to predict the response of species to the effects of environmental change, whether they will adapt to the new environmental conditions or shift their range tracking their preferred environment (e.g. Sillero et al, 2014;Lagerholm et al, 2017). Despite the evident potential of this combined approach, it is still rarely used to understand the distribution and adaptation capacity of insect pests.…”
Section: Understanding the Distribution Dynamics Of Insect Pestsmentioning
confidence: 99%
“…Thus, patterns of variation in present-day samples can be used to infer changes that occurred in the past; however, samples from natural history collections provide the opportunity to study genetic and phenotypic changes in species directly. Thus, these type of samples are very valuable in ascertaining the effects of ecological or environmental events on the genetic variation of species (Mikheyev et al, 2015;Carew et al, 2016;Fountain et al, 2016;Holmes et al, 2016;Lagerholm et al, 2017;Ruane & Austin, 2017). Collection samples within an agricultural landscape context represent a unique tool to obtain a more comprehensive insight into the selective forces that shape pest diversity and distribution dynamics and, in this way deliver information that can be used to monitor better and control crop pests.…”
Section: The Use Of Sample Collections To Understand Ecological and Ementioning
confidence: 99%
“…The Japanese rock ptarmigans (L. m. japonica) is an endemic subspecies of Japan and their habitat is limited to the high mountain area of middle Honshu island, where is the southernmost range of this species (Baba et al 2001). Although the phylogeographic studies of this species were carried out (Holder et al 2000;Caizergues et al 2003;Lagerholm et al 2017), the origin of Japanese rock ptarmigans is little known. Here, we determined the complete mitogenome of Japanese rock ptarmigans and carried out the phylogenetic analysis among the Lagopus muta and its related species.…”
mentioning
confidence: 99%
“…The rock ptarmigans from Iceland and Siberia formed a clade with 100% bootstrap probability and Japanese rock ptarmigans were placed as sister lineage of this clade. Lagerholm et al (2017) suggested Siberian, Arctic insular (Greenland, Svalbard, and Iceland) and North American populations are genetically close each other and form a distinct group from European population. Although only three rock ptarmigans (Siberia, Iceland, and Japan) were used in this study, our result suggests Japanese rock ptarmigans are old lineage before the rock ptarmigans spread to whole Siberia, Arctic islands, and North America.…”
mentioning
confidence: 99%